Hegels Logik der Wirklichkeit und ihre Bedeutung für die praktische Philosophie (Revista Eletrônica Estudos Hegelianos, 2022)
We observe that recently the topics of Hegel research refer more and more to his "real-philosophical" works and his lectures on the philosophy of law in order to attach questions of practical philosophy to them, for instance in relation to feminism, postcolonialism, Critical Race Theory, climate change, etcetera. In this essay, I do not want to participate in these debates in terms of content, but to show that the real relevance of Hegel for practical philosophy does not lie in cherry-picked quotations from the mentioned works, but in the deep analysis of the part of his main work in which he systematically develops the basic themes of practical philosophy: in the section on actuality (Wirklichkeit) in Science of Logic. Central topics such as freedom, subjectivity, power, violence, etc. are being discussed here and presented in their inner logic. Hegel himself referred to this part of his Logic in defense of his much criticized statement that the rational is actual and vice versa. I will therefore trace the line of argumentation of this important section and discuss from it some consequences for practical or political philosophy. In doing so, it will become apparent that some of the current disputes regarding Hegel’s theoretical as well as political positions are rather classifications within the boundaries of "understanding" thinking (verständiges Denken), beyond which Hegel’s dialectics has long since passed.